Using regional bird density distribution models to evaluate protected area networks and inform conservation planning. Issue 5 (8th May 2017) - Alexander, John D.; Stephens, Jaime L.; Veloz, Sam; Salas, Leo; Rousseau, Josée S.; Ralph, C. John; Sarr, Daniel A.
Abstract: As data about populations of indicator species become available, proactive strategies that improve representation of biological diversity within protected area networks should consider finer‐scaled evaluations, especially in regions identified as important through course‐scale analyses. We use density distribution models derived from a robust regional bird abundance dataset, coupled with habitat conservation plans, to evaluate a network of protected areas and to inform conservation and biodiversity planning in the greater Klamath Siskiyou Bioregion, an area recognized globally as a region of outstanding biological diversity. Our novel modeling approach allowed for comparisons of abundance of conservation focal species on federal vs. non‐federal lands, federal lands that are protected to maintain natural habitats vs. federal lands managed for multiple uses, and seven protected areas of interest. Our comparisons highlight conservation opportunities for suites of species associated with coniferous forests, oak woodlands, and grasslands. Specifically, we found that species associated with oak woodland and grassland habitats, both habitats of conservation concern, were not well represented in the Bioregion's existing protected areas. These species would benefit from expanding the regional protected area network to include their associated at‐risk habitats. In contrast, our results suggest that coniferous forests birds are well represented in the Bioregion's protected areas. We identify management opportunities specifically associated with the restoration of fire‐adapted ecosystems that would benefit coniferous forest focal species on both federally protected areas and other multiple‐use lands. Our analysis provides an example of how a finer‐scaled evaluation of a regional protected area network adds value to course‐scale evaluations of protected areas and biological diversity. Data and results from this research were used to inform science‐based expansion of the Bioregion's network of protected areas.